Leadership in Action: Image Counts: Building an Authentic Leadership Presence - Criswell, Corey; Campbell, David (Center for Creative Leadership, 2008)
A leader's image can be either an asset or a liability. Although many leaders mistakenly believe that managing their image amounts to chicanery, it's important for them to recognize the genuine aspects of themselves that should be coming across to other people-but may not be. Crafting an authentic image requires you to gain a clear picture of the image people are currently perceiving, decide what image you would like to portray, and develop the skills to close the gap.
Keywords: Leadership